The effectiveness of poverty alleviation policy: Why is the quality of institutions the bane in Nigeria? - Fisayo Fagbemi; Babafemi Oladejo; Opeoluwa A. Adeosun (African Governance and Development Institute (AGDI), 2020)
The article examines the nexus between the quality of institutions and the poverty in Nigeria over the period 1984-2017, using Dynamic Ordinary Least Squares, Canonical Cointegrating Regression and Vector Error Correction Mechanism. The analysis based on three institutional measures (bureaucratic quality, democratic accountability and rule of law) reveals how poverty rate could be escalated by entrenched poor governance. The evidence shows that democratic accountability and rule of law are significant for poverty reduction. This reinforces the assertion that accountability and transparency coupled with strict adherence to rule of law in the public sector are the principal components of poverty alleviation. Also, findings reveal that poverty and weak institutions are interconnected and mutually reinforcing in the country. Overall, the findings posit that poverty is widespread in Nigeria due to capacity constraints of public institutions or underlying governance practices. By implication, the article suggests that policymakers should focus on measures that have the greatest leverage for enhancing effective governance oriented towards poverty reduction and development. In addition, tackling socioeconomic inequalities, curbing political unrest and building strong institutions are central to ensuring a socially sustainable basis for holistic welfare improvements.
Keywords: 330; Governance; public institutions; poverty alleviation; cointegration analysis; Nigeria